PEDAGOGICAL FOUNDATIONS FOR IMPROVING ASSESSMENT SYSTEMS IN EDUCATION THROUGH INFORMATION TECHNOLOGIES - Samijonov Azizbek Ismoiljon ugli (Modern American Journals, 2025)
This article explores the pedagogical foundations of improving assessment systems in higher education through the integration of information technologies. Assessment is a critical component of the educational process, determining the quality of teaching and learning outcomes. Traditional assessment methods, while valuable, are often insufficient in meeting the demands of the digital age. Therefore, the implementation of digital assessment systems—including online testing platforms, e-portfolios, remote monitoring, artificial intelligence-based evaluation tools, and adaptive learning technologies—is becoming an essential pedagogical requirement. Drawing on international practices and local experiences, this article analyzes the advantages of digital assessment systems, their impact on students’ cognitive and creative abilities, and proposes methodological recommendations for the effective improvement of assessment in higher education.
Keywords: Digital assessment, higher education, information technologies, e-learning, monitoring, artificial intelligence, adaptive learning.